"Behold, There Were Twins in Her Womb" (Gen. 25:24-26; 38:27-30): Medical Science and the Twin Births in Genesis - Makujina, John ca. Ende 20. Jh./Anfang 21. Jh. (Tyndale bulletin, 2017)
Eran Viezel claims that the book of Genesis is ignorant of the fundamentals of childbirth, particularly the presenting foetal member. While the head normally emerges first, Genesis mistakenly thinks that the hands present, as they do in livestock deliveries. Therefore, the veracity of the twin births in Genesis 25:24-26 and 38:27-30, where a hand exits the womb first (Jacob and Zerah), should be rejected. The present article, however, exposes significant inaccuracies and unsupported assumptions on Viezel's part. Moreover, while maintaining that both births are anomalous, this article proposes medically realistic scenarios for the parturitions of the twins in Genesis.